2007
DOI: 10.14236/ewic/hci2007.11
|View full text |Cite
|
Sign up to set email alerts
|

yExploring Potential Usability Gaps when Switching Mobile Phones: An Empirical Study

Abstract: The present study explores potential usability gaps when users switch from a familiar to an unfamiliar mobile phone interface. A within-subject experiment was performed in which nine users familiar with Sony-Ericsson T630 and nine familiar with Nokia 7250 performed tasks on both phones. On average, test subjects spent more time on finishing tasks with an unfamiliar phone than with a familiar one. For two of the four tasks, there was a significant difference in completion time between the first-time Nokia users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Karahanna et al's (1999) research also supports this position, as users find an IT easier to use with experience. With frequent mobile phone usage, a mental model of how it works is established by the user (Yamashita, Barendregt, & Fjeld, 2007), and it is expected that the same happens with smartwatches. As it happens with most repetitive behaviours, the cognitive processing eventually disperses and leads to routinized behaviour (Bargh, 1994;Logan, 1989;.…”
Section: H8a Habit (Hab) Moderates the Effect Of Satisfaction (Sat) O...mentioning
confidence: 99%
“…Karahanna et al's (1999) research also supports this position, as users find an IT easier to use with experience. With frequent mobile phone usage, a mental model of how it works is established by the user (Yamashita, Barendregt, & Fjeld, 2007), and it is expected that the same happens with smartwatches. As it happens with most repetitive behaviours, the cognitive processing eventually disperses and leads to routinized behaviour (Bargh, 1994;Logan, 1989;.…”
Section: H8a Habit (Hab) Moderates the Effect Of Satisfaction (Sat) O...mentioning
confidence: 99%
“…The results showed that the layout of information influences mental models and UI design based on users' mental models is necessary to improve usability. Yamashita et al [26] studied the usability gap when users changed from a cell phone familiar with the operation to a cell phone that is not. The users of Sony and Nokia cell phones were asked to perform an operation task for each cell phone.…”
Section: Introductionmentioning
confidence: 99%